2017
DOI: 10.1094/pdis-05-16-0609-re
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Environmental Factors Related to Claviceps purpurea Ascospore Production in Perennial Ryegrass Seed Fields and Development of Predictive Models

Abstract: Claviceps purpurea, the causal agent of ergot of perennial ryegrass seed crops, overwinters as sclerotia in the soil and releases airborne ascospores in the spring that infect flower ovaries and replace seed with sclerotia. Burkard spore traps were used to quantify the dispersal phenology and concentration of ascospores in perennial ryegrass seed fields in the Columbia Basin of Oregon. Weather factors were measured concurrently with spore trapping. Nonparametric regression, box-and-whisker plots, and univariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…While the mean for ergot occurrence was higher in 2014 (Table 1), the highest individual value was found in 2013, where nearly all recovered material was ergot (95%). Precipitation was higher and temperatures cooler in 2014, most likely enhancing the disease [44].…”
Section: Long-term Yield Potentialmentioning
confidence: 99%
“…While the mean for ergot occurrence was higher in 2014 (Table 1), the highest individual value was found in 2013, where nearly all recovered material was ergot (95%). Precipitation was higher and temperatures cooler in 2014, most likely enhancing the disease [44].…”
Section: Long-term Yield Potentialmentioning
confidence: 99%
“…Air and soil temperatures in the spring can affect the timing, duration, and quantity of capitula production during host anthesis (Markhasseva, 1936). Research in the lower Columbia Basin of Oregon revealed that most ascospores were observed when minimum soil temperatures were between 61.2 and 68.7°F and maximum soil temperatures were between 67.3 and 79.0°F (Dung et al., 2017). Air temperature, which is often easier to measure than soil temperature, was also strongly correlated with ascospore production events.…”
Section: Ergot Biology and Epidemiology In Grass Seed Cropsmentioning
confidence: 99%
“…A degree‐day model that predicted ergot ascospore presence in the lower Columbia Basin of Oregon was developed using such data from perennial ryegrass seed crops in the lower Columbia Basin of Oregon (Dung et al., 2017). On average, the degree‐day model accounted for 93% of ascospores produced during the grass seed production season in the region.…”
Section: Ergot Biology and Epidemiology In Grass Seed Cropsmentioning
confidence: 99%
“…Air and soil temperatures in the spring can affect the timing, duration, and quantity of capitula production during host anthesis (Markhasseva, 1936). Research in the lower Columbia Basin of Oregon revealed that most ascospores were observed when minimum soil temperatures were between 61.2 and 68.7°F and maximum soil temperatures were between 67.3 and 79.0°F (Dung et al, 2017). Air temperature, which is often easier to measure than soil temperature, was also strongly correlated with ascospore production events.…”
Section: Ergot Biology and Epidemiology In Grass Seed Cropsmentioning
confidence: 99%
“…A degree-day model that predicted ergot ascospore presence in the lower Columbia Basin of Oregon was developed using such data from perennial ryegrass seed crops in the lower Columbia Basin of Oregon (Dung et al, 2017). On average, the degree-day model accounted for 93% of ascospores produced during the grass seed production season in the region.…”
Section: Ergot Biology and Epidemiology In Grass Seed Cropsmentioning
confidence: 99%